An Analysis of Thematic Development Pattern in Thesis Abstracts by Undergraduate English Education Students of Universitas Bengkulu Academic Year 2019 - Nur Indah Lifah; Syafrizal Sabaruddin; Alamsyah Harahap (Universitas Bengkulu, 2020)
This research is aimed to find the types and the mostly applied of thematic development pattern, also to describe students writing an abstract. The research was designed as a descriptive qualitative. The data of this research was abstract by undergraduate English education students of Universitas Bengkulu academic year 2019 with totally 20 abstracts. The data was collected by using documentation on studetns’ thesis in 2019 meanwhile 2 undergraduate English education student was taken as interviewed. The data was analyzed by using identification, coding, tabulation, interpretation, and conclusion. This thematic progression model using the Paltridge 2006 models will be chosen as a theoretical analytical framework. The data was analyzed by using identification, coding, tabulation, interpretation, and conclusion. The results showed that Simple Linear Progression (SLP), Constant Theme Progression (CTP), and Split Rheme Progression (SRP) were found in thesis abstract. Furthermore, the constant theme progression (CTP) was the mostly applied. The order of occurrence was as follows: constant theme (69.4%), simple linear theme (25%), and split rheme (5.6%). It is also found that the researchers are not able to study existing standard patterns, they just write based on what the guidance from their lecturer. On the other hand, they writing an abstract without following other guidance such as a book which is contain how to write a good abstract. It is concluded that the researcher is not independent in abstract writing. Moreover, this is because lecturers will decide and acceptable their abstracts.